If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 1 = 3x + 4 Reorder the terms: 1 + 6x = 3x + 4 Reorder the terms: 1 + 6x = 4 + 3x Solving 1 + 6x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + 6x + -3x = 4 + 3x + -3x Combine like terms: 6x + -3x = 3x 1 + 3x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + 3x = 4 + 0 1 + 3x = 4 Add '-1' to each side of the equation. 1 + -1 + 3x = 4 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 4 + -1 3x = 4 + -1 Combine like terms: 4 + -1 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| y+15=-30 | | x-2x+12-3x=-5(x-2)+2 | | 8+3n=-2a+24 | | 2x-6-8=0 | | 4-2x=8+.5x | | -4x-3=6x-123 | | -0x+10-3x=-5(x-2)+2 | | x+22+3x=-19-3x-22 | | -2x+9-3x=-5(x-2)+2 | | -2x+12-3x=-5(x-2)+0 | | -2x+12-3x=5(x-2)+2 | | 4+3x=7x-24 | | 3(s+2)-(2s-3)=5 | | 3x^2-3x=21 | | 3x+8y+2=0 | | 4x=(-8) | | 5/8*8/5 | | -2x+12-3x=-5(x-2)+3 | | 2x+12-2x=-5(x-2)+2 | | 4x+3y-5=0 | | 8+3x=6x+26 | | -4x+12-2x=-5(x-2)+2 | | x+6-x-4=10-x | | 6x+y=8x-2y | | 4x+2(x+1)=26 | | 12(7X-1)-8(6X+1)+(5X+3)11=23(4X-X)+23 | | -1x+12-3x=-5(x-2)+1 | | 2+3x=5x+24 | | 5/2=17/3 | | 3x+7x=850 | | 0=ln(x^2+5)+0.5x+1 | | -2x+12-2x=-5(x-1)+2 |